Mono Acyl Glycerol Compound Synthesis Through Partial Transesterification Of Castor Oil (Ricinus communis L.) using KOH as Catalyst - Ratu, Marlin; Nitbani, Febri O.; Ola, Pius Dore (Chemistry Notes, 2019)
It has been done a study of mono acyl glycerol compound synthesis through partial transesterification of castor oil (Ricinus communis L.) using KOH as catalyst. The product of mono acyl glycerol obtained is 45.4 % with the ratio between castor oil triglyceride and methanol 1:2 at 35 0C temperature with the amount of catalyst 0.5 % (b/b) from the reactant total weight and the reaction time 30 minutes. In this research, it was done a compound characterization using, TLC, FTIR and LC MS to prove the success of targeting compound has been synthesized.